First enantiospecific synthesis of (-)-heritol: absolute configuration determination - Chavan, Subhash P.; Thakkar, Mahesh; Kalkote, Uttam R. (Tetrahedron Letters, 2007)
The first enantiospecific synthesis of (-)-heritol, from naturally occurring (R)-(+)-citronellal and confirmation of its absolute configuration, is described. (c) 2006 Elsevier Ltd. All rights reserved.